Faster monitoring of the invasive alien species (IAS) Dreissena polymorpha in river basins through isothermal amplification - Joana Carvalho (Nature Portfolio, 2021)
Abstract Zebra mussel (Dreissena polymorpha) is considered as one of the 100 most harmful IAS in the world. Traditional detection methods have limitations, and PCR based environmental DNA detection has provided interesting results for early warning. However, in the last years, the development of isothermal amplification methods has received increasing attention. Among them, loop-mediated isothermal amplification (LAMP) has several advantages, including its higher tolerance to the presence of inhibitors and the possibility of naked-eye detection, which enables and simplifies its potential use in decentralized settings. In the current study, a real-time LAMP (qLAMP) method for the detection of Dreissena polymorpha was developed and tested with samples from the Guadalquivir River basin, together with two real-time PCR (qPCR) methods using different detection chemistries, targeting a specific region of the mitochondrial gene cytochrome C oxidase subunit I. All three developed approaches were evaluated regarding specificity, sensitivity and time required for detection. Regarding sensitivity, both qPCR approaches were more sensitive than qLAMP by one order of magnitude, however the qLAMP method proved to be as specific and much faster being performed in just 9 min versus 23 and 29 min for the qPCR methods based on hydrolysis probe and intercalating dye respectively.